Safety and Efficacy of Using Advanced Hybrid Closed Loop Off-Label in an Infant Diagnosed with Permanent Neonatal Diabetes Mellitus: A Case Report and a Look to the Future - Federico Pezzotta; Nicola Sarale; Giordano Spacco; Giacomo Tantari; Enrica Bertelli; Giulia Bracciolini; Andrea Secco; Giuseppe d'Annunzio; Mohamad Maghnie; Nicola Minuto; Marta Bassi (MDPI AG, 2024)
The case report shows the safety and efficacy of insulin treatment with Advanced Hybrid Closed Loop (AHCL) system in a young patient affected by permanent neonatal diabetes mellitus (PNDM) due to chromosome 8 deletion syndrome involving the GATA4 gene. In the first days of life, he presented hyperglycaemia and started an intravenous insulin infusion therapy, replaced by a continuous subcutaneous insulin infusion (CSII) with Medtronic Minimed 780G® insulin pump (Medtronic, Northridge, CA, USA). At the age of 2 years, the off-label activation of SmartGuard® automated insulin delivery mode led to a great improvement in glycaemic control, reaching all recommended targets. At the 1-month follow-up visit, Time in Range (TIR) increased from 66% to 79%, with a Time in Tight Range (TTIR) of 55% and a reduction of 11% in time in hyperglycaemia and of 2% in time in hypoglycaemia. During the entire follow-up, no episodes of ketoacidosis or severe hypoglycaemia were observed and the patient maintained the glycaemic recommended targets reached at 1 month. Maintaining optimal glycaemic control and reducing hyperglycaemia are essential for brain growth and neurocognitive development in young patients. AHCL use should be considered to ensure good glycaemic control in patients affected by neonatal diabetes.